Resistensi Obat Aspirin Terhadap Pasien Penyakit Jantung Koroner: Sebuah Literature Review - Mally Ghinan Sholih; Munir Alinu Mulki; Ain Luthfiannisa; Esti Syahrin; Moza Aulia Syifni; Muhammad Naufal Nurhadi Hidayat; Safira Rosyidah; Salma Alviyah; Muhammad Raka Tresna (Journal of Pharmaceutical and Sciences, 2023)
In Indonesia, coronary heart disease is the largest contributor to mortality with a prevalence related to cardiovascular disease. Using drugs from a combination of fibrinolytics, anticoagulants, and antiplatelets can overcome acute coronary heart disease. The most commonly used therapy is the antiplatelet class in the form of aspirin as a treatment for the management of cardiovascular disease and its prevention. However, several studies have stated that aspirin is a conventional antiplatelet which sometimes has the potential to cause failure and is ineffective for the treatment of coronary heart disease, so that it can be said to be aspirin resistance. Article writing method review This study uses scientific literature. The steps taken begin with collecting various journal references through the database PubMed Identifier (PMID), google schoolar, and science direct within the last 10 years (2013-2023). The keyword in the literature search is aspirin resistance, aspirin resistance coronary disease, and aspirin coronary heart diseases. Based on the results of reviews that have been reviewed, it shows that there are resistance mechanisms and factors that influence aspirin resistance in coronary heart disease patients.